Advances in civil structures : selected peer reviewed papers from the 3rd International Conference on Civil Engineering, Architecture and Building Materials (CEABM 2013), May 24-26, 2013, Jinan, China - Tian, Li (Lecturer in civil engineering) (Applied mechanics and materials ;, 2013)
Collection of selected, peer reviewed papers from the 2013 International Conference on Civil, Architecture and Building Materials (3rd CEABM2013), May 24-26, 2013, Jinan, China. This set of 346 peer reviewed papers covers the subject areas of Structural Engineering, Monitoring and Control of Structures, Structural Rehabilitation, Retrofitting and Strengthening, Reliability and Durability of Structures.